2012
DOI: 10.1007/s00423-012-1032-7
|View full text |Cite
|
Sign up to set email alerts
|

IONM-guided goiter surgery leading to two-stage thyroidectomy—indication and results

Abstract: We have shown a significant difference in the rate of bilateral RLNP when comparing termination and continuation of a bilateral procedure after primary IONM signal loss. We strongly recommend a two-stage thyroidectomy after signal loss on the primary side of resection in benign bilateral goiter surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 27 publications
4
82
0
8
Order By: Relevance
“…If the procedure is staged at that point, however, the risk does not increase any further . Our findings support the idea that IONM is a reliable tool for avoiding increasing the risk of bilateral nerve injury beyond that caused by injury on the side of initial dissection . Functional dynamic information afforded through neural monitoring allows the surgeon an opportunity to make surgical decisions based on full knowledge of the situation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…If the procedure is staged at that point, however, the risk does not increase any further . Our findings support the idea that IONM is a reliable tool for avoiding increasing the risk of bilateral nerve injury beyond that caused by injury on the side of initial dissection . Functional dynamic information afforded through neural monitoring allows the surgeon an opportunity to make surgical decisions based on full knowledge of the situation.…”
Section: Discussionsupporting
confidence: 75%
“…The American Thyroid Association Surgical Affairs Committee consensus statements on outpatient thyroid surgery and management of goiters agrees that neural monitoring helps confirm intact neural function and may play a role in discharge planning . Given IONM's function in prognostication of postoperative neural function, it has been suggested that it may guide decision to stage bilateral thyroid and central neck surgery when loss of RLN signal on initial side of dissection is detected . To date, there are very little published data regarding reliability, safety, and practicality of using IONM feedback to stage the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral RLN injury, the most dreaded complication, can be avoided by intraoperative neuromonitoring. Neuromonitoring predicts postoperative vocal fold function and allows changing operative strategy to a two-stage thyroidectomy if necessary [6, 7]. Unilateral postoperative vocal fold palsy rates have, however, not been reduced by intermittent intraoperative neuromonitoring (I-IONM) [1, 4, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the case of intraoperative LOS on the first‐operated side in a planned total thyroidectomy, the thyroid surgeon essentially has three options for surgery on the contralateral side if RLN function is intact. Figure summarizes the three options Perform staged surgery on the second side.…”
Section: Discussionmentioning
confidence: 99%